Sepsis : Definitions, Pathophysiology and the Challenge of Bedside Management - Ward, Nicholas S.; Levy, Mitchell M. (Springer International Publishing : Imprint: Humana Press, 2017)
This book is designed to provide a comprehensive and state-of-the-art resource for clinicians who care for patients with sepsis and research scientist alike, . Patients with severe sepsis requiring ICU admission have very high rates of ICU and overall hospital mortality, with estimates ranging from 18 to 50%. Risk factors for death from sepsis include underlying illness, increased age, and multi-system organ failure. This is compounded by the significant variation in the management of early severe sepsis. Care of these patients and clinical conditions can be quite complex, and materials are collected from the most current, evidence-based resources. Book sections have been structured to review the overall definitions and epidemiology of sepsis as well as current insights into the pathophysiology of sepsis. This review summarizes the evidence for the international consensus guidelines for the identification and management of sepsis. The latter part of this book reviews emerging concepts and approaches in the diagnosis and management of sepsis that may significantly reduce mortality in the future. Sepsis: Pathophysiology, Definitions and the Challenge of Bedside Management represents a collaboration between authors drawn from a variety of disciplines and contributions from basic scientists and highly recognized clinical opinion leaders with expertise in clinical trials.
Keywords: Medicine.; Critical care medicine.; Respiratory organs -- Diseases.; elektronické knihy; electronic books